Until the wilting day: an analysis of urban population changes in provincial cities in Thailand from 2010 to 2019. Issue 3 (4th May 2023) - Bamrungkhul, Settawut; Tanaka, Takahiro
ABSTRACT: Population change is an important indicator of city status and can guide urban planning. Based on population changes, each city is categorised as "a growing city, " "a stagnant city, " or "a shrinking city." Although shrinking and stagnant cities are common, city planning based on the pro-growth paradigm often omits them, causing negative impacts on the performance of urban policy, especially in less-developed countries. To fulfil the limited understanding of the population changes in those countries, this study aims to investigate the population change patterns between 2010 and 2019 using provincial cities in Thailand as a case study. All the provincial cities were categorised based on their annual population change rate. Cluster analysis was performed to categorise sub-clusters based on the status of urban population concentration and its changes. The results reveal that, although Thailand is rapidly urbanising, only 7 out of 76 provincial cities are in the growing city cluster. Most provincial cities are in the stagnant or shrinking city cluster, with urban concentration decline happening as a result. This evidence indicates that several provincial cities may be shrinking. Related government organisations should shift the paradigm of urban management based on population changes.